BUDGET REALIZATION AS A MANAGEMENT CONTROL TOOL FOR COMPANY PERFORMANCE AT PT. PELABUHAN INDONESIA I (PERSERO) PEKANBARU BRANCH - Benny Napitupulu; Sudarno Sudarno; Achmad Tavip Junaedi (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
One way to define the company's goals is to create a plan, one that cost planning is essential in the operation of the company activity. Preparation, control, until the realization of the budget is an important factor in the control of management. Good management control will be reflected from a sound budget planning from start budgeting to realization in which the control of the use of the budget includes the cost of the company. The purpose of this study was to determine the function of a planning application to the realization of budget costs play an important role in the management control process in order to achieve the goals set previously by the company. The research was conducted by the author at. PT. Indonesian Harbor I (Persero) Pekanbaru located at Saleh Abbas 3 Pekanbaru. The results of this study show that the variance resulting from budget planning to the realization greatly affects the level of management control of the company. In other words, the efficiency of which is determined by the value of variance budget planning process as well as cost control processes that will better demonstrate the value of the level of management control of the company.